Bubble continuous positive airway pressure machine versus indigenous bubble continuous positive airway pressure as a respiratory support in preterm babies with respiratory distress syndrome: a prospective outcome research at a tertiary care centre in Gujarat, India - Thaddanee, Rekha; Chaudhari, Ankur; Chauhan, Hasmukh; Morbiwala, Shamim; Khilnani, Ajeet Kumar (International Journal of Contemporary Pediatrics, 2018)
Background: In India, there is high burden of prematurity in newborns due to high birth rate and lack of good antenatal care. The objective of this study was to compare the outcome (efficacy and safety) of Bubble Continuous Positive Airway Pressure (B-CPAP) machine and Indigenous Bubble Continuous Positive Airway Pressure (I-CPAP) as a primary mode of respiratory support in preterm new-borns with respiratory distress syndrome (RDS). It was a prospective observational comparative study conducted at NICU of a tertiary care teaching hospital of western Gujarat, India, from December 2016 to July 2017. Methods: Eighty-one preterm babies <36 weeks of gestation age with respiratory distress (Silverman Anderson scoring >4) within 6 hours of birth were included (out of 182 preterm newborns with respiratory distress syndrome) and put on respiratory support either with B-CPAP machine (n = 48) or with I-CPAP (n = 33). Outcome was compared in the form of CPAP failure, survival and complication rates. Results: There was no significant difference in the demographic profile of patients in both groups except number of neonates between 1.5-2.5 kg birth weight were significantly high in B-CPAP (45.8%) compared to I-CPAP (33.3%) (p = 0.00074). There were no significant differences in CPAP failure rates in B-CPAP (27%) versus I-CPAP (24.2%). The survival rate (72.9% in B-CPAP) versus (75.7% in I-CPAP) in both groups was also similar (CI 95%, p = 0.774). The complications, such as moderate to severe nasal septal damage, occurred significantly more frequent with B-CPAP machine (47.9%) than on I-CPAP (6%) (CI 95%, p = 0.000062). Conclusions: Efficacy of I-CPAP as a primary mode of respiratory support for preterm new-born with respiratory distress was comparable to B-CPAP. The ease with which it can be assembled makes it a suitable alternative to B-CPAP.